Symbolic Interaction in Tiktok's Live Streaming: A Study of Influencer-Viewers Engagement - Melani, Elsa Rakhma; Ahmad Zamzamy (Jurnal Spektrum Komunikasi, 2023)
In the contemporary digital landscape, social media has evolved into a pervasive phenomenon, serving as a medium for communication and interaction in the virtual realm, liberated from the confines of space and time—epitomized by the omnipresent live streaming feature. TikTok, distinguished by its live streaming functionality, emerges as the paramount social media platform, attracting users ranging from influencers to artists. Central to social media interaction is the adept representation of communicative intentions. This research probes the intricacies of TikTok's live streaming feature as a symbolic interaction medium between influencers and their audience. Employing a qualitative descriptive methodology, the researcher elucidates insights derived from in-depth interviews and observations. The study is anchored in Herbert Mead's symbolic interactionism, with a specific focus on the dimensions of mind, self, and society. Findings spotlight that influencers, within the realm of the mind concept, prioritize augmenting their follower count, with some anticipating financial contributions from the audience to address familial needs. Within the self-concept domain, a subset of influencers directs attention to leveraging symbolic features of live streaming to express their self-concept. Symbols such as likes, comments, shares, and viewers are regarded as potent conveyors of messages pertaining to identity and emotions, particularly within the micro-influencer domain. Concurrently, the audience tends to emulate the self-concept of the influencers they follow. In the societal context, unanimity prevails among informants regarding the imperative adherence to collectively endorsed rules and norms, notably the regulatory policies instituted by TikTok for live streaming.